“Message in A Bottle”: Discovering Fanilect within Taylor Swift’s Fandom - Dinda Khoirunnisa; Nurenzia Yannuar; Yazid Basthomi; Nanang Zubaidi (Journal of Language and Literature, 2025)
This study delves into the use and impact of fanilect, a specialized form of language, within Taylor Swift’s fandom on TikTok. By employing discourse analysis, it examines the various forms and functions of fanilect in this digital community. The findings reveal four key types of fanilect: jargon, which consists of specific terms and phrases used only within the fan group; intertextual references, where fans incorporate Taylor Swift's lyrics or cultural references into their interactions; routine interactions, such as repeated behaviors or phrases during events or online discussions; and multimodal communication where fans express themselves through a combination of text, images, and videos. Furthermore, the study identifies fanilect's roles in shaping the dynamics within the Swiftie fandom. First, it contributes to identity formation, helping fans identify themselves as part of the community. Second, it establishes power structures, where knowledge of fanilect signifies status within the fandom. Third, fanilect fosters community building by encouraging emotional connections and shared experiences. Lastly, it enhances creative expression, allowing fans to engage with the fandom in varied and artistic ways. This research provides critical insights into how fanilect influences community interactions and identity within Taylor Swift’s fanbase, offering broader implications for understanding linguistic practices in digital fan cultures.